Estimates of Certain Integral Inequalities on Time Scales - Deepak B. Pachpatte (Journal of Mathematics)
The main objective of this paper is to establish explicit bounds on certain integral inequalities on time scales, which can be used as tools in the study of certain classes of integral equations on time scales. Some applications of our results are also given.